Effect of Phenotypic Screening of Extracts and Fractions of Erythrophleum ivorense Leaf and Stem Bark on Immature and Adult Stages of Schistosoma mansoni. (7th June 2018) - Kyere-Davies, Gertrude; Agyare, Christian; Boakye, Yaw Duah; Suzuki, Brian M.; Caffrey, Conor R.
Abstract : Schistosomiasis is a disease caused by a flatworm parasite that infects people in tropical and subtropical regions of Sub-Saharan Africa, South America, China, and Southeast Asia. The reliance on just one drug for current treatment emphasizes the need for new chemotherapeutic strategies. The aim of this study was to determine the phenotypic effects of extracts and fractions of leaf and stem bark of Erythrophleum ivorense (family Euphorbiaceae), a tree that grows in tropical parts of Africa, on two developmental stages of Schistosoma mansoni, namely, postinfective larvae (schistosomula or somules) and adults. Methanol leaf and stem bark extracts of E. ivorense were successively fractionated with acetone, petroleum ether, ethyl acetate, and methanol. These fractions were then incubated with somules at 0.3125 to 100 μ g/mL and with adults at 1.25 μ g/mL. The acetone fractions of both the methanol leaf and bark of E. ivorense were most active against the somules whereas the petroleum ether fractions showed least activity. For adult parasites, the acetone fraction of methanol bark extract also elicited phenotypic changes. The data arising provide the first step in the discovery of new treatments for an endemic infectious disease using locally sourced African medicinal plants.